Evaluation of Electrical Discharge Machining parameters on energy saving and machining characteristic enhancement of biodegradable AZ31 Magnesium Alloy - Norizwan Juraimi (Tanjong Malim, 2024)
Evaluation of Electrical Discharge Machining parameters on energy saving and machining characteristic enhancement of biodegradable AZ31 Magnesium Alloy by Norizwan Juraimi